Patient-Centered Communication for Discussing Oncotype DX Testing. (27th May 2016) - Roberts, Megan C.; Bryson, Amy; Weinberger, Morris; Dusetzina, Stacie B.; Dinan, Michaela A.; Reeder-Hayes, Katherine E.; Wheeler, Stephanie B.
ABSTRACT: Oncotype DX testing (ODX), a tumor gene expression test, may improve breast cancer care, however, communicating results remains challenging. We identified patient-centered communication strategies/gaps for discussing ODX results. We applied a patient-centered communication framework to analyze qualitative interviews with oncologists about how they communicate about ODX with patients, using template analysis in Atlas.ti. Overall, providers discussed four patient-centered communication domains: exchanging information, assessing uncertainty, making decisions and cross-cutting themes. Providers did not report discussing emotional aspects of managing uncertainty, assessing decision-making preferences, and evaluating decisions. A patient-centered approach may be a model for communicating about tumor gene expression tests.